John Strachey - Thompson, N. author. aut Link
XI, 288 p.
Keywords: This book studies John Strachey, one of the most important left intellectuals in twentieth century Britain. It provides a detailed exposition of his intellectual evolution set in its historical context, thus highlighting the options, pressures, dilemmas and pitfalls besetting British socialists in the turbulent times of the inter and post-war periods.